Pengembangan Media Monopoli dalam Meningkatkan Motivasi serta Minat pada Mata Pelajaran IPS Kelas 7 SMP - Muhammad Fikry; Muhammad Naharuddin Arsyad; Nurcholis Sunuyeko (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The inclusion of Hindu-Buddhist history in the Social Studies (IPS) curriculum plays a pivotal role in fostering historical thinking skills among students. However, the reality at SMP Sunan Ampel Poncokusumo Malang suggests that the IPS learning process on this subject matter often relies heavily on lecture-based methods, failing to engage students actively. While discussion methods have been introduced to address this issue, a comprehensive presentation of the historical material has yet to be achieved. Therefore, the researchers undertook the development of the IPS learning process at SMP Sunan Ampel Poncokusumo. This study aims (1) to elucidate the development of monopoly learning media in enhancing student motivation and interest in IPS subjects, and (2) to explain the evaluation results of the development of monopoly learning media in improving student motivation and interest in IPS subjects. The method used in this design is developmental research utilizing the ADDIE planning technique. The design process comprises five stages: analysis, design, development, implementation, and evaluation. Based on the validation results from subject matter experts and media experts, including IPS teachers from the school and experts from Insan Budi Utomo University in Malang, it can be concluded that the Monopoly media development received a final assessment of 87.5% from media and subject matter expert validation, falling under the "highly valid" category. Meanwhile, the student response questionnaire yielded a score of 88%, meeting the criteria of "excellent." The monopoly learning media that has been developed meets validity standards both in terms of media and material, so it can be concluded that the use of monopoly learning media can increase students' motivation and interest in learning in social studies learning.